Prompt penetration and substorm effects over Jicamarca during the September 2017 geomagnetic storm - Fejer, B. G. (2021)
We used reanalyzed Jicamarca radar measurements to study the response of equatorial ionospheric electrodynamics and spread F during the main phase of the large September 2017 geomagnetic storm. Our observations near dusk on 7 September show very large upward drifts followed by a large short-lived downward drift perturbation that completely suppressed the lower F region plasma irregularities and severely decreased the backscattered power from the higher altitude spread F. We suggest that this large short-lived westward electric field perturbation is most likely of magnetospheric origin and is due to a sudden and very strong magnetic field reconfiguration. Later in the early night period, data indicate large, mostly upward, drift perturbations generally consistent with standard undershielding and overshielding electric field effects, but with amplitudes significantly larger than expected. Our analysis suggests that occurrence of storm-time substorms is one of the major factors causing the large nighttime westward and eastward electric field perturbations observed at Jicamarca near the storm main phase. Our analysis also suggests that magnetospheric substorms play far more important roles on the electrodynamics of the equatorial nighttime ionosphere than has generally been thought.